Unraveling the Origins of Fatigue in Hafnia Ferroelectric Capacitors - Hyeon-Seo Do; Ik-Jyae Kim; Jiwoung Choi; Jang-Sik Lee (IEEE Journal of the Electron Devices Society)
This study investigates the role of positively charged oxygen vacancies in the central region of ferroelectric capacitors and their impact on fatigue. It has been found that, during fatigue, positively charged oxygen vacancies accumulate in the central region, leading to significant degradation in device performance. The application of a high-voltage recovery pulse effectively reverses the charge state of these vacancies from positive to neutral and redistributes them uniformly across the device, restoring its performance. This recovery process is analogous to the ‘wake-up’ state of the device, demonstrating its potential to restore electrical performance. The results of this study emphasize the importance of controlling the charge state and distribution of oxygen vacancies in the central region to enhance the durability and functionality of ferroelectric devices. This work provides a pathway for the broader and more effective application of ferroelectric materials in advanced semiconductor devices.